Incentives for Sustainable Consumption and Production: Economic and Legal Instruments - Čiegis, Remigijus; Gineitienė, Dalia (Ekonomika, 2004)
Sustainable consumption and production are essential for sustainable development. In this article, legal and economic requirements for the development of sustainable consumption and production are analysed. First, the concept of sustainable consumption is briefly discussed. Then sustainable consumption problems are discussed within the context of ecological economics. After this more basic part, regulation requirements and economical instruments for the development of sustainable consumption and production are elaborated.